STRATEGI KEPEMIMPINAN KEPALA SEKOLAH DALAM MENINGKATKAN KOMPETENSI PROFESIONAL GURU DI UPT SPF SMP NEGERI 7 MAKASSAR - Jumiati Jumiati; Syamsurijal Basri; Hasan Hasan (JURNAL ILMIAH PENELITIAN MAHASISWA, 2025)
This study discusses the principal’s leadership strategies in improving the professional competence of teachers at UPT SPF SMP Negeri 7 Makassar. The purpose of this research is to identify the strategies used by the principal to enhance teachers’ professional competence at UPT SPF SMP Negeri 7 Makassar. This study employs a descriptive qualitative approach, with the principal and teachers serving as the primary sources of data. Data were collected through interviews, documentation, and observation. The collected data were then analyzed through several stages, namely data collection, data reduction, data presentation, and drawing final conclusions. The validity of the data was ensured through triangulation techniques. The research findings indicate that the principal implements three main strategies to improve teachers’ professional competence: (1) encouraging teachers to participate in scientific activities such as workshops, seminars, and training; (2) involving teachers in professional organizations such as MGMP, as well as in regular supervision and coaching activities; and (3) implementing teacher development programs, including internal training such as In House Training (IHT), workshops, and technical assistance in the use of learning technologies. These strategies are carried out in a planned and continuous manner to enhance teachers’ content mastery, application of innovative teaching methods, and professional responsibility. However, in practice, the principal faces challenges such as limited teacher time, low motivation among some teachers, and insufficient support in terms of facilities and funding. Despite these obstacles, the principal continues to strive to optimize teacher roles and participation through a collaborative approach and continuous development.